Conserving bird biodiversity : general principles and their application - Norris, Ken, 1963-; Pain, Deborah J. (Conservation biology series (Cambridge, England), 2002)
In order to slow or stop the unprecedented loss of biodiversity, conservationists need reliable information on which to base conservation or restoration programmes. Using bird conservation to illustrate the basic scientific principles and applying this to real problems, this book is essential reading for students and researchers in conservation biology.